2012
DOI: 10.2116/analsci.28.367
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Inorganic Cations by Capillary Ion Chromatography with a Non-suppressed Contactless Conductivity Detector

Abstract: A non-suppressed capillary ion chromatographic method with a laboratory-made packed cation-exchange column (100 mm × 0.32 mm i.d.) was developed for the separation and simultaneous determination of five common inorganic cations (sodium, ammonium, potassium, magnesium and calcium). Cation exchangers were prepared by the reaction of the hydroxyl group on the surface of diol-group bonded silica gel with 1,3-propanesultone in methanol. Simultaneous separation of these five common inorganic cations were achieved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This value showed the satisfactory preformances reproducibility of the AS‐hybrid monolith. Based on this result, the AS‐hybrid monolith in our study showed better improvement on performance than in other previous literatures that determination of common inorganic cations using diol‐group bonded silica gel with 1,3‐propanesultone , which indicated that the AS‐hybrid monolith columns had exceptional reproducibility, and the preparation of organic‐inorganic hybrid monolithic column using “one‐pot” approach manner was feasible.…”
Section: Resultssupporting
confidence: 64%
“…This value showed the satisfactory preformances reproducibility of the AS‐hybrid monolith. Based on this result, the AS‐hybrid monolith in our study showed better improvement on performance than in other previous literatures that determination of common inorganic cations using diol‐group bonded silica gel with 1,3‐propanesultone , which indicated that the AS‐hybrid monolith columns had exceptional reproducibility, and the preparation of organic‐inorganic hybrid monolithic column using “one‐pot” approach manner was feasible.…”
Section: Resultssupporting
confidence: 64%
“…Using the sample preparation conditions outlined in Section 2.2.3, limit of quantifications (LOQs) were found to be between 5 and 22 μg/ml. These values were higher than the LOQ values obtained by another NMR method that was developed to quantify cations in mineral water with LOQs of 1.39 mg/L for Ca 2+ and 0.87 mg/L for Mg 2+ and by flame atomic absorption spectrometry and ion chromatography . However, to achieve a lower LOQ, several options are possible.…”
Section: Resultsmentioning
confidence: 68%
“…Shen et al reported the determination of inorganic anions and cations in bench‐top IC systems employing monolithic columns . Rong et al reported the separation of inorganic cations on a packed capillary column . C 4 D continues to be used as a diagnostic tool in the characterization of monolithic chromatographic columns for IC and HPLC .…”
Section: C4d In Other Flow‐through Methodsmentioning
confidence: 99%